Water Resources Potential Assessment during Dry Season in Indonesia: A Systematic Literature Review - Hadian, Mohamad Sapari Dwi; Suhardiman, Sani; Firmansyah, Yusi; Barkah, Mochamad Nursiyam; Sunarie, Cecep Yandri; Ramadian, Aldrin (Journal of Ecohumanism, 2024)
The dry season in Indonesia has been studied in the context of its impact on rainfall extremes, with research indicating that the dry season rainfall extremes are strongly affected by IOD and ENSO (El Niño-Southern Oscillation). The impact of dry season in 2023 based on the data from the Meteorological, Climatological, and Geophysical Agency (BMKG ) mentioned that this dry season started from march to September 2023. Java Island, whose land area is only 138,379 km² or 7 (seven) percent of Indonesia's area, has a very important position because it is crowded by 65 percent of Indonesia's population or an average of 864 people / km² and contributes to GNP of 60 percent. This article aims to review the water resources in Java Island in Indonesia during the dry season in 2017 to 2023. That causes the lack of water resources has become the main problem in some area in Java Island in Indonesia. This research result assesses the water resources during the dry season, the technique, the method, and the findings. There are 287 articles found only from Scopus sources, 40 article reviewed, and only 5 articles have been matched to the topic by using Prisma P. process. Finally, the result shows that one aspect that remains unclear about Indonesia's dry season is how exactly climate change influences its duration and intensity. While it's known that Indonesia undergoes a dry season, the specific impacts of climate change on factors like rainfall patterns, temperature, and the occurrence of extreme weather events are not fully grasped. This lack of understanding presents challenges for planning agriculture, managing water resources, and conserving ecosystems in the region.